Dieback of blackthorn (Acacia mellifera subsp. detinens) in South West Africa - Schreuder, Wouter (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1988.